Tirofiban, a Glycoprotein IIb/IIIa Antagonist, Has a Protective Effect on Decompression Sickness in Rats: Is the Crosstalk Between Platelet and Leukocytes Essential? - Lambrechts, Kate; de Maistre, Sébastien; Abraini, Jacques H.; Blatteau, Jean-Eric; Risso, Jean-Jacques; Vallée, Nicolas (Frontiers in Physiology, 2018)
In its severest forms, decompression sickness may extend systemically and/or induce severe neurological deficits, including paralysis or even death. It seems that the sterile and ischemic inflammatory phenomena are consecutive to the reaction of the bubbles with the organism and that the blood platelet activation plays a determinant role in the development of decompression sickness. According to the hypotheses commonly put forward, the bubbles could either activate the platelets by direct contact or be the cause of abrasion of the vascular epithelium, which would expose the basal plate glycogen and then prompt the platelets to activate. The purpose of this study is to confirm anti-platelet drugs specific to GPIIb/IIIa integrin could prevent decompression sickness, using a rat model. There is a significant difference concerning the incidence of the drug on the clinical status of the rats (p=0.016), with a better clinical outcome for rats treated with tirofiban (TIR) compared with the control rats (p=0.027), even if the three anti-GPIIb/IIIa agents used have limited respiratory distress. Tirofiban limited the decrease in platelet counts following the hyperbaric exposure. Tirofiban help to prevent from DCS. Tirofiban is specific to GPIIb/IIIa whereas eptifibatide and abciximab could inhibit αVβ3 and αMβ2 involved in communication with the immune system. While inhibiting GPIIb/IIIa could highlight a platelet-dependent inflammatory pathway that improves DCS outcomes, we wonder whether inhibiting the αVβ3 and αMβ2 communications is not a wrong approach for limiting mortality in DCS.